Analysis Of The Relationship Between Knowledge, Attitude And Oral Health Behavior And Numbers Dental Caries - yanti, rahma; Erawati, Suci; Sitepu, Rahmadani; Aritonang, Barita; Mala Sari, Nur (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: Dental caries is an oral health problem that is of global concern, where dental caries is a dental disease characterized by damage to the tooth surface and if left untreated, the infection will spread to the pulp. The impact is changes in tooth structure, pain and infection and death of the pulp. There are 57 students out of 83 new undergraduate students in 2023 at the Faculty of Islamic Economics and Business experiencing dental caries, this case has always been a common dental problem, but it must be reduced to a very low number of cases. Objective: to determine the relationship between knowledge, attitudes and oral health behavior and the rate of dental caries in new students at the Faculty of Economics and Islamic Business, UIN North Sumatra, Medan. Methodology: The research method is observational analytics with a cross sectional approach, a sample of 287 respondents, data collection methods using observation and questionnaires. Results: there is a relationship between knowledge and the number of dental caries (? = 0.000), there is a relationship between attitudes and the number of dental caries (? = 0.000), and there is a relationship between behavior and the number of dental caries (? = 0.000). Discussion: behavior is the most dominant factor influencing the rate of dental caries ? = 0.002, OR value 26.903, and C.I 95% (3.250 – 222.684). Conclusion: Faculty to create a joint policy with university clinics in the form of an oral health program. Students are expected to know, behave well, and apply oral health behavior.